Evidence for Strain-Specific Exometabolomic Responses of the Coccolithophore Emiliania huxleyi to Grazing by the Dinoflagellate Oxyrrhis marina - Poulson-Ellestad, Kelsey L.; Harvey, Elizabeth L.; Johnson, Matthew D.; Mincer, Tracy J. (Frontiers in Marine Science, 2016)
The coccolithophore Emiliania huxleyi forms massive blooms and plays a critical role in global elemental cycles, sequestering significant amounts of atmospheric carbon dioxide on geological time scales via production of calcium carbonate coccoliths and emitting dimethyl sulfoniopropionate (DMSP) which has the potential for increasing atmospheric albedo. Because grazing in pelagic systems is a major top-down force structuring microbial communities, the influence of grazers on E. huxleyi populations has been of interest to researchers. Roles of DMSP (and related metabolites) in interactions between E. huxleyi and protist grazers have been investigated, however, little is known about the release of other metabolites that may influence, or be influenced by, such grazing interactions. We used high-resolution mass spectrometry in an untargeted approach to survey the suite of low molecular weight compounds released by four different E. huxleyi strains in response to grazing by the dinoflagellate Oxyrrhis marina. Overall, a strikingly small number of metabolites were detected from E. huxleyi and O. marina cells, but these were distinctly informative to construct metabolic footprints. At most, E. huxleyi strains shared 25% of released metabolites. Furthermore, there appeared to be no unified metabolic response in E. huxleyi strains to grazing; rather these responses were strain specific. Concentrations of several metabolites also positively correlated with grazer activities, including grazing, ingestion, and growth rates; however, no single metabolite responded uniformly across all strains of E. huxleyi tested. Regardless, grazing clearly transformed the constituents of dissolved organic matter produced by these marine microbes. This study addresses several technical challenges, and presents a platform to further study the influence of chemical cues in aquatic systems and demonstrates the impact of strain diversity and grazing on the complexity of dissolved organic matter in marine systems.